Party Systems, Political Competition, and Inequality in Subnational Brazil - Vincent Mauro (Latin American Research Review, 2021)
Many have attributed the recent unprecedented wave of redistribution in Brazil to national economic and political factors such as the commodities boom, changes in minimum wages or premiums to skilled labor, the rise of the Partido dos Trabalhadores and President Luiz Inácio Lula da Silva and a commodities-driven economic boom. Yet much less attention has been devoted to the study of inequality at the subnational level, where trajectories of inequality across states remain incredibly varied. This article argues that Brazil’s most recent democratic transition enhanced political competition in many Brazilian states, which in turn has contributed to the amelioration of inequality. Using an original time-series cross-sectional dataset covering the highly redistributive period of 1998–2015, this article finds that Brazilian states with higher political and party competition have lower levels of inequality than those with less competitive party systems.   Resumo Muitos atribuíram a onda recente de renda redistribuição no Brasil por fatores econômicos e politicais nacionais como o ‘boom de commodities,’ câmbios no salários-mínimos, prêmios mais baixos para mão de obra qualificada, e a ascensão do Partido dos Trabalhadores e o Presidente Luiz Inácio Lula da Silva. Embora, muito menos atenção foi dedicada para a pesquisa de desigualdade no nível subnacional, onde niveles relativos de desigualdade através os estados permanecem incrivelmente variados. Esse artigo faz o argumento que a transição democrática mais recente no Brasil aumentada competição em os sistemas de partidos de alguns estados, que por sua vez contribuiu para a melhoria de desigualdade. Utilizando dados do período 1998–2015, assim como análise qualitativa um par de estados, Pará e Rio Grande do Sul, esse artigo encontra os estados brasileiros com sistemas partidos mais competitivo são mais prováveis para avançar politicais de sociais e ter niveles mais baixos de desigualdade que outros com sistemas partidos menos competitivos.